The Effectiveness of Goal Setting Training in Increasing Learning Motivation among Students at X High School - Sahila, Syarifatus; Laily, Nadhirotul (Universitas Negeri Padang, 2025)
This study aims to examine the effectiveness of goal setting training in increasing students’ learning motivation. The research used a quantitative approach with a pre-experimental one-group pretest–posttest design. Seventeen grade XI students of SMA X with initially very low to low learning motivation participated in two training sessions of goal setting. Data were collected using the Learning Motivation Scale adaptation. Data analysis using the Paired Sample T-Test showed a significant increase in learning motivation scores (t(16) = –14.213, p < 0.001) with a very large effect size (Cohen’s d = 3.45). The results indicate that goal setting training effectively improves both students’ motivation and positive learning behavior.